Renkoho: Maintaining a Flexible Body for Health & Longevity (Revista de Artes Marciales Asiáticas, 2012)
For nearly sixty years Murakami Katsumi (b. 1927) has been a practitioner of Okinawa Karatedo and martial arts. He also studied Chinese martial arts under Sato Kinbei (b. 1926). Yet despite his advanced years, he still moves like a much younger man, a tribute to his diligence in pursuing martial arts as both a physical, mental, and spiritual discipline. This article is excerpted from his book Karate no Kokoro to Waza (The Spirit and Techniques of Karate) and details the exercises he has created to prepare the body for martial art training and extending one’s life through the practice of good health. All the exercises demonstrated in this article are performed by the original author.